Harmonics Analysis of Input Current of 3-Phase PWM Rectifier - Alfin Prima Adjie; Muhammad Imran Hamid (Andalas Journal of Electrical and Electronic Engineering Technology, 2021)
Rectifier is a non-linier load that causes harmonic distortion in the power system. Pulse-width modulation (PWM) method is an effective method in pressing the magnitude of harmonics in a rectifier application, it provides an almost sinusoidal input current. However, the variation of loads that supplied by a rectifier cause the harmonics that arise can still beyond the applicable standard. The amount of harmonics in the operating range of a rectifier need to be identified to determine the filter on the input side. In this research article, 3-phase PWM rectifier was designed with hysteresis current control technique using PSCAD software simulation. Harmonic compensation was carried out by applying an active filter based on P-Q theory to reduce the harmonic distortion that occurs in the input current, thus giving a low total harmonic distortion (THD) value. Based on the simulation, 3-phase PWM rectifier operation starting at a power level of 150 kW, giving a THD value above 5-10% by the increasing the amount of load supplied by the rectifier. The application of active filter based on the P-Q theory is able to compensate harmonics in the input current wave with a THD value below 5% in the rectifier operating range.